Ultrastructure of Connective Tissue Cells of Giant African Snails Achatina fulica (Bowdich) - Viyada Seehabutr (Agriculture and Natural Resources, 2002)
The connective tissue sheath of cerebral ganglion of giant African snails Achatina fulica (Bowdich) contain many types of cells such as pore cells, granular cells, vesicular connective tissue cells, amoebocytes, fibroblasts and muscle cells. Pore cells are characterized by numerous invagination of the cell membrane. Granular cells contain numerous granules. The vesicular connective tissue cells contain round nuclei, located in the centre of the cells. Amoebocytes have pseudopodia. Fibroblasts are spindle-shaped or elongate cells. They contain ovoid or elongate nuclei. Muscle cells have ovoid nuclei located in the centre of the cells.